Surgical management of a vomeropremaxillary fracture in a patient with complete bilateral cleft lip and palate following trauma - Karan Sharma; Shalvi Singh; Puneet Batra; S C Sood (Wolters Kluwer Medknow Publications, 2018)
Timing of treatment of protruding premaxilla in a bilateral cleft lip and palate (BCLP) patient is an issue of dilemma. Fracture of the premaxillary segment following trauma in a patient with complete BCPL is presented. Salvaging the mobile premaxilla becomes an emergency. Surgical management of such a fracture has been discussed in a patient with repaired cleft lip and palate in the light of recent literature.